Implementasi ORESTE dengan Basson Rank untuk pemilihan tempat kursus TOEFL di Yogyakarta - Femi Dwi Astuti; Siska Lidya Revianti (Komunitas Dosen Indonesia, 2023)
TOEFL is one of the most frequently used international standardized tests for registering for masters and doctoral degrees, seeking study scholarships or for promotions. Unfortunately, there are still many students and employees who still experience difficulties in taking the TOEFL test. This is what then becomes the reason for them to take English courses, especially to prepare themselves for preparing the TOEFL test. Yogyakarta, which has the title of